Synthesis and characterization of novel N,N-di(ethyl)-N’-benzoylthiourea complexes of Pd(II), Pt(II), Cu(II) and Zn(II) bearing phenanthroline ancillary ligand [MII(diimine)(L-кO,S)]+ as potentially anticancer agents - Matiti, Lindela (My University, 2021)
A series of acylthioureato complexes of Pd(II), Pt(II), Cu(II), and Zn(II) bearing phenanthroline-based ancillary ligands were investigated in this study. The target complexes were prepared by the reaction between a phenanthroline-substituted precursor complex and the N,N-di(ethyl)-N’-benzoylthiourea in the presence of a deprotonating agent. The target complexes were isolated as atmospherically stable solids with a yield ranging from 45 – 60%. Complete characterization of these acylthioureato complexes includes 1D and 2D nuclear magnetic resonance spectroscopy, infrared spectroscopy, mass spectrometry, elemental analysis, and single-crystal X-ray diffraction (where applicable). These complexes were screened against A549 lung carcinoma and HEK-293 embryotic kidney cancer cell lines. For the complex cytotoxicity effect, two concentrations were used (100 μM and 10 μM). MTT assay together with an organic solvent (DMSO: EtOH) was used to solubilize the cells. Evaluation of these complexes was done by exposing them to the cell for 24 hours and the absorbance was recorded. Most of the complexes were highly active against the HEK-293 cancer cell line at 100 μM with 90-100 cell-death. However, the [Zn(phen)(L-кO,S)Cl] variation complex was the least active at 100 μM with cell viability of 40%. [Cu(phen)(L-S,O)]Cl was the most active compound against the A549 lung carcinoma cancer cell-line with less than 1% cell viability at 100 μM and less than 20% cell viability at 10 μM and which can be assumed for the copper influence. There was a significant improved cytotoxicity effect for complexes bearing methyl in 5 and 6 positions of the 1,10-phenanthroline than those with unsubstituted 1.10-phenanthroline. When comparing square-planar complexes from the PGM group (Pd and Pt), we found that Pt(II) displayed the highest activity. Three zinc complexes were compared to each other for their cytotoxicity effect, substituted phen was observed to be the most active followed by the acetate coordinated complex, and chloride variation been the least active. [Cu(phen)(L-S,O)]Cl compound was found to be the most active compound and its Cu(II) complexes bearing mixed ligand diimine and acylthioureato are not yet mentioned as an anti-cancer drug, which makes the novel interesting to start acylthiourea and diimine ligand variation and test IC50 for the structural relationship with DNA interaction.
A dissertation submitted to the Faculty of Science, Witwatersrand University, Johannesburg, In fulfilment of requirement for the degree of Master of Science (MSc) in Chemistry, 2021